2001
DOI: 10.1016/s1097-2765(01)00323-9
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of PTEN Transcription by p53

Abstract: PTEN tumor suppressor is frequently mutated in human cancers and is a negative regulator of PI3'K/PKB/Akt-dependent cellular survival. Investigation of the human genomic PTEN locus revealed a p53 binding element directly upstream of the PTEN gene. Deletion and mutation analyses showed that this element is necessary for inducible transactivation of PTEN by p53. A p53-independent element controlling constitutive expression of PTEN was also identified. In contrast to p53 mutant cell lines, induction of p53 in pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
644
4
13

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 828 publications
(687 citation statements)
references
References 29 publications
26
644
4
13
Order By: Relevance
“…Because PTEN can be transactivated by p53 (Stambolic et al, 2001), and we previously found Figure 2a, both p53 and PTEN protein levels were reduced by Id-1 and these changes were restored by suppression of Id-1 using retroviral antisense construct (left). These mRNA levels were also downregulated by Id-1, suggesting that Id-1 regulated both p53 and PTEN at the transcriptional level ( Figure 2b).…”
Section: Id-1 Inhibits Pten Transcription Through P53 Downregulationmentioning
confidence: 71%
See 2 more Smart Citations
“…Because PTEN can be transactivated by p53 (Stambolic et al, 2001), and we previously found Figure 2a, both p53 and PTEN protein levels were reduced by Id-1 and these changes were restored by suppression of Id-1 using retroviral antisense construct (left). These mRNA levels were also downregulated by Id-1, suggesting that Id-1 regulated both p53 and PTEN at the transcriptional level ( Figure 2b).…”
Section: Id-1 Inhibits Pten Transcription Through P53 Downregulationmentioning
confidence: 71%
“…C-Jun binds to the AP-1 site of the PTEN promoter and can suppress its transcription, whereas Egr-1 activates PTEN transcription by direct binding to the PTEN 5 0 untranslated region (Virolle et al, 2001). In addition, p53 has been reported as a crucial PTEN transactivator (Stambolic et al, 2001). It was also reported that suppression of p53 mutant expression is involved in upregulation of p21 and PTEN (Vikhanskaya et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Suppression of the IGF-1 receptor is accompanied by reduced IGF-1R and IRS-1 (a downstream modulator of IGF-1R signaling) tyrosine phosphorylation (Ohlsson et al, 1998). P53 also upregulates PTEN transcription, a tumor suppressor and lipid/tyrosine phosphatase that inhibits phosphatidylinositol 3-kinase (PI3K) function downstream of IGF-1 (Figure 1) (Stambolic et al, 2001). Finally, p53 also directly suppresses PI3K function by inhibiting p110 alpha, a subunit of the PI3K complex .…”
Section: How Does the Dna Damage Response Suppress Igf-1 Signaling?mentioning
confidence: 99%
“…In this regard, p53-inducible gene PTEN (Stambolic et al, 2001) or Siah-1L (Matsuzawa and Reed, 2001;Iwai et al, 2004) reduces cellular levels of b-catenin. Absence of PTEN protein suppresses the phosphorylation of b-catenin via inactivation of GSK3b.…”
Section: Ccdc85b Competes With B-catenin For Tcf4mentioning
confidence: 99%